PERSEPSI MASYARAKAT TERHADAP KINERJA LEMBAGA KESEHATAN PADA SEKTOR PELAYANAN PENGOBATAN TRADISIONAL DI KABUPATEN PURWAKARTA - Putra, Risa Kota; Ratnasari, Dewi; Septiwi, Rizki Eka (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: Indonesia has a variety of traditional medical heritage that has the potential to be developed, ironically the Indonesian market is flooded with imported traditional medicine from various countries from mainland Asia, especially from China and India. Government in the field of regulation has sufficiently provided a legal basis, legal certainty, legal protection, quality improvement, safety, and benefits for traditional empirical health services and complementary traditional health services. But the reality of its implementation in the regency / city has not been felt by the side of the health institutions towards the Indonesian traditional medicine, especially in Purwakarta Regency. Objective: Exploring public perceptions related to the performance of health institutions in the field of traditional medicine based on gender diversity, education level, health / non-health profession and respondent age. Method: This research is a type of qualitative associative explanative research in communities that are connected with health care facilities. Subjects were 137 people in Purwakarta Regency, West Java Province. The selection and sampling uses the conditional sampling method, which is analyzed according to the Ridwan scale (2009). Retrieval of data using a questionnaire. Results: The results of this study showed that the performance of health institutions in Purwakarta was explosively associative perceived as weak in the traditional medicine sector with the highest score (strong: 70.35% or cumulative 78%) on the Ridwan scale (2009) by female respondents aged 40 years above, education has never gone to college, and is a non-health profession, when compared to respondents with other criteria. Conclusion: All groups of respondents perceive with a strong score on the Ridwan-2009 scale (62.5% or cumulative 74.0%), namely the weak performance of health institutions based on all variables assessed explosively associative that includes impartiality, scarcity of higher education and research, not yet standardized and weak guidance in the traditional medicine sector in Purwakarta Regency.